MACROECONOMIC STRESS-TESTING OF MORTGAGE DEFAULT RATE USING A VECTOR ERROR CORRECTION MODEL AND ENTROPY POOLING - Ardia, David; Guerrouaz, Anas; Rey, Jeanne (Assurances et gestion des risques / Insurance and Risk Management, 2016)
We propose a methodology to perform macroeconomic stress-testing on the probability of default of a given borrowers’ population (i.e., aggregate probability of default) through simulation from a vector error correction model and entropy pooling (Meucci, 2008).